2017
DOI: 10.15376/biores.12.3.5001-5016
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Depolymerization of Alkali Lignin in Sub- and Super-critical Ethanol

Abstract: The effects of reaction parameters on catalytic depolymerization of alkali lignin in sub-and super-critical ethanol were investigated using a high pressure autoclave, and the liquid oil and solid char products were characterized. The experimental data indicated that Rh catalysis, controlling reaction conditions at ethanol critical temperature (240 ºC) and pressure (7.0 MPa), high ethanol/water ratios (100/0), and the medium reaction time (4 h) enhanced the depolymerization of alkali lignin to liquid oil and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Depolymerization of lignin has also been performed using sub-and supercritical ethanol, methanol, and combined with water. This study showed that ethanol can significantly enhance the depolymerization of lignin and decrease char formation [150]. This result may be due to the formation of hydrogen radicals from the ethanol, which is coupled with the intermediates from lignin and inhibits the repolymerization reaction intermediates from forming char.…”
Section: Depolymerization Of Lignin Using Sub-and Supercritical Fluidsmentioning
confidence: 82%
See 1 more Smart Citation
“…Depolymerization of lignin has also been performed using sub-and supercritical ethanol, methanol, and combined with water. This study showed that ethanol can significantly enhance the depolymerization of lignin and decrease char formation [150]. This result may be due to the formation of hydrogen radicals from the ethanol, which is coupled with the intermediates from lignin and inhibits the repolymerization reaction intermediates from forming char.…”
Section: Depolymerization Of Lignin Using Sub-and Supercritical Fluidsmentioning
confidence: 82%
“…Supercritical methods have been used since the 1990s, and during the initial stage of their use, KL and OL were treated with supercritical methanol [73]. Different types of sub-and supercritical fluids, such as water [149], ethanol [150], and carbon dioxide [151], have been used. Condensation is very common in depolymerization, but supercritical depolymerization reactions are highly efficient at preventing condensation.…”
Section: Depolymerization Of Lignin Using Sub-and Supercritical Fluidsmentioning
confidence: 99%
“…For the purpose of further improving the yield of lignin monomers, Tong and co-workers investigated the reaction conditions for the depolymerization of alkali lignin in sub-and supercritical ethanol via Raney Ni and Rh/C catalysts. 95 It has been concluded that Raney Ni and Rh/C could both prevent the refusion of lignin spheres during the reaction, which favored the occurrence of depolymerization, thereby increasing the liquid oil yield. Struven et al performed the lignin hydrocracking under subcritical water conditions and found that Raney Ni could perform almost complete demethoxylation of methoxyphenol moieties.…”
Section: Catalytic Conversion Of (Hemi)cellulose and Thementioning
confidence: 99%
“…Running the reaction in supercritical solvent is ideal to prevent condensation reactions and increase the oil yield of lignin. For the purpose of further improving the yield of lignin monomers, Tong and co-workers investigated the reaction conditions for the depolymerization of alkali lignin in sub- and supercritical ethanol via Raney Ni and Rh/C catalysts . It has been concluded that Raney Ni and Rh/C could both prevent the refusion of lignin spheres during the reaction, which favored the occurrence of depolymerization, thereby increasing the liquid oil yield.…”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 99%
“…Главным ограничением для применения процессов гидрогенолиза лигнина являются процессы реполимеризации и коксообразования, которые приводят не только к снижению конверсии, но и к дезактивации катализатора за счет образования на его поверхности инертного слоя кокса. Замедлить скорости этих нежелательных процессов можно, проводя процесс гидрогенолиза в среде сверхкритических растворителей [12].…”
unclassified